AB0528 Cost-effectiveness of a humanized anti-interleukin-6 (IL-6) receptor monoclonal antibody, tocilizumab, in rheumatoid arthritis using IORRA cohort database. (23rd January 2014) - Tanaka, E.; Inoue, E.; Hoshi, D.; Kobayashi, A.; Sugimoto, N.; Shidara, K.; Sato, E.; Seto, Y.; Nakajima, A.; Momohara, S.; Taniguchi, A.; Yamanaka, H.
Abstract : Background: Tocilizumab, a humanized anti-IL-6 receptor monoclonal antibody, has been developed as a treatment for rheumatoid arthritis (RA). It was first approved in Japan in April 2008, and thereafter in Europe and the US. Although substantial evidence has accumulated regarding the efficacy and safety of tocilizumab for RA, the high cost has been a heavy financial burden for both RA patients and society. No prior research has been conducted concerning the cost-effectiveness of tocilizumab based on clinical data in daily practice. Objectives: To examine the cost-effectiveness of tocilizumab for patients with RA using the IORRA cohort database. Methods: We conducted a Markov model-based simulation to estimate the cost-effectiveness of tocilizumab (TCZ group) compared with methotrexate alone (MTX group). Patients receiving TCZ or MTX were extracted using the matching method from the IORRA participants, and data from these patients were used to determine most of the model parameters.Health states were defined based on the levels of physical dysfunction according to the J-HAQ (Japanese version of HAQ) score, which were assumed to be associated with costs and utility, and transition probabilities between these states were assumed to differ among the two groups. All parameters in the model including drug change or discontinuation rate, mortality rate, utility score and direct and indirect costs were based on clinical data from the IORRA cohort. Lifetime cumulative costs and quality-adjusted life years (QALYs) were estimated using Monte Carlo simulation in both groups, and the incremental cost-effectiveness ratio (ICER) of tocilizumab was calculated. We used 5.0 million JPY (1 EUR =100 JPY in January 2012) as the allowable threshold of ICER. The time horizon was the lifetime of the cohort, the initial population of 10, 000 patients created by random sampling from patient data extracted from IORRA. Utilities and costs were discounted annually at 3.0%. We also conducted a probabilistic sensitivity analysis. Results: The lifetime cumulative costs and QALYs were 35.4 million JPY and 11.7 in the TCZ group and 23.3 million JPY and 9.3 in the MTX group, respectively. The average period of low physical dysfunction (J-HAQ <1.1) was longer in the TCZ group (8.3 years) than in the MTX group (5.3 years). The ICER for tocilizumab was 4.94 million JPY, with a 66.2% probability of falling below the allowable threshold by probabilistic sensitivity analysis. Conclusions: This study has demonstrated the cost-effectiveness of tocilizumab for the first time, based on data from a large observational cohort representing daily clinical practice in Japan. Disclosure of Interest: E. Tanaka: None Declared, E. Inoue: None Declared, D. Hoshi: None Declared, A. Kobayashi: None Declared, N. Sugimoto: None Declared, K. Shidara: None Declared, E. Sato: None Declared, Y. Seto: None Declared, A. Nakajima: None Declared, S. Momohara: None Declared, A. Taniguchi: None Declared, H. Yamanaka Grant/Research support from: IORRA study is supported from 40 pharmaceutical companies; Asahikasei Kuraray Medical Co., Ltd., Abbott Japan Co., Ltd., Asahikasei Pharma Corporation, AstellasPharma Inc., AstraZeneca K.K., Bristol-Myers Squibb, Chugai Pharmaceutical Co., Ltd., Daiichi Fine Chemical Co., Ltd., Daiichi Sankyo Co., Ltd., Dainippon Sumitomo Pharma Co., Ltd., Eisai Co., Ltd., GlaxoSmithKline K.K., Hisamitsu Pharmaceutical Co., Inc., Janssen Pharmaceutical K.K., Japan Tobacco Inc., Kaken Pharmaceutical Co., Ltd., Kissei Pharmaceutical Co., Ltd., Kowa Pharmaceutical Co.Ltd., Maruho Co., Ltd., Mitsubishi Chemical Medience Corporation, Mitsubishi Tanabe Pharma Corporation, Mochida Pharmaceutical Co. Ltd., MSD K.K., Mundipharma K.K., Nippon Chemiphar Co., Ltd., Nippon Shinyaku Co., Ltd., Novartis Pharma K.K., Otsuka Pharmaceutical Co., Ltd., Pfizer Japan Inc., Sanofi-Aventis K.K., Santen Pharmaceutical Co., Ltd., Sanwa Kagaku Kenkyusho Co., Ltd., Sekisui Medical Co., Ltd., Shionogi Co., Ltd., Taishotoyama Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co. LTD., Teijin Pharma Limited, Torii Pharmaceutical Co., Ltd., UCB Japan Co. Ltd., ZERIA Pharmaceutical Co., Ltd., Consultant for: Abbott, AstraZeneca, Bristol-Myers Squibb, Chugai, Eisai, Janssen, Mitsubishi Tanabe., Pfizer, Takeda, Teijin Pharma, UCB